Line-field confocal optical coherence tomography for high-resolution noninvasive imaging of skin tumors - Dubois, Arnaud; Levecq, Olivier; Azimani, Hicham; Siret, David; Barut, Anaïs; Suppa, Mariano; Del Marmol, Véronique; Malvehy, Josep; Cinotti, Elisa; Rubegni, Pietro; Perrot, Jean-Luc (Journal of biomedical optics, 2018)
An optical technique called line-field confocal optical coherence tomography (LC-OCT) is introduced for high-resolution, noninvasive imaging of human skin in vivo. LC-OCT combines the principles of time-domain optical coherence tomography and confocal microscopy with line illumination and detection using a broadband laser and a line-scan camera. LC-OCT measures the echo-time delay and amplitude of light backscattered from cutaneous microstructures through low-coherence interferometry associated with confocal spatial filtering. Multiple A-scans are acquired simultaneously while dynamically adjusting the focus. The resulting cross-sectional B-scan image is produced in real time at 10  frame  /  s. With an isotropic spatial resolution of ∼1  μm, the LC-OCT images reveal a comprehensive structural mapping of skin at the cellular level down to a depth of ∼500  μm. LC-OCT has been applied to the imaging of various skin lesions, in vivo, including carcinomas and melanomas. LC-OCT images are found to strongly correlate with conventional histopathological images. The use of LC-OCT as an adjunct tool in medical practice could significantly improve clinical diagnostic accuracy while reducing the number of biopsies of benign lesions.